A Stability Indicating Assay Method Development and Validation for the Frovatriptan Succinate Monohydrate by Using UV: A Spectrophotometric Technique. (2nd May 2013) - Verma, Hitesh; Verma, Surajpal; Singh, Harmanpreet
Abstract : A new simple, reliable, inexpensive, and accurate method was developed for the quantification of Frovatriptan Succinate Monohydrate in different physiological media at 244 nm in bulk and in tablet dosage forms. The developed method is an attempt to surpass the disadvantages associated with the reported methods, namely, less sensitive and tedious in usage for routine purposes. Beer's law was followed over the range of 1.0 µg/mL to 4.5 µg/mL. Stability indicating assay method was developed and validated as per the ICH guidelines using various parameters, for example, accuracy, precision, limit of quantification, limit of detection, robustness, ruggedness, solution stability, recovery, forced degradation (hydrolysis, photo degradation, thermal degradation, and oxidation), and so forth. Percent relative standard deviation associated with all the parameters was less than 2, showing compliance with the acceptance criteria of ICH guidelines. The developed method was very sensitive as limit of quantification and limit of detection were found to be 0.025 µg/mL and 0.00625 µg/mL, respectively. Forced degradation studies of drug reveal good stability under the chosen experimental conditions.